Use of Internet by Universities Teachers and Benefits in Teaching and Scientific Research (Journal of the College of Education for Women, 2019)
The research aims to shed light on the internet and how to employ them and to take advantage of applications in scientific research among faculty members, from a survey the opinions of professors at the University of Alanbar and Almustansiriah, to see the reality of use of the Internet and ways to invest in the service of scientific research.The follow descriptive analysis approach , which is appropriate to the nature of this study concerned with exploring the views on the uses of the Internet. The study reached the field the following results:1- There are(60) % of respondents use the Internet on an ongoing basis to see new information and keep pace with scientific developments in the field of specialty and the average use of the Internet( 3) h per day for the respondents.2- The proportion of % 73of respondents believed that the Internet channel of communication and scientific research is indispensable for the professor.3- The study also showed that %50 of respondents believe that the culture of rational use of the Internet could raise the level of return to the informational and cognitive researcher.The study came up with several recommendations, the most important are:1 - The need to visit sites of scientific continuously for the purpose of obtaining information that serve the scientific research2 - The need to contain information use of the Internet for the purpose of raising awareness to deal with the internet data to be a way of building and learning and excellence does not demolished3 - Making electronic locations for the universities and colleges and other scientific research centers.